Elements of aesthetics in the Bible. Characterization test (The Bible as a meeting place for Christian denominations, 2022)
This paper deals with the issue of religious aesthetics in the Bible on the example of the analysis of Franz Rosenzweig’s thought, selected biblical themes and rabbinic literature. It briefly discusses Rosenzweig’s essay The Mystery of the Style of Biblical Stories. According to the author, the Bible does not cease to influence the next generations of mankind through the category of beauty. From biblical literature discussed are: 1 Maccabees, the Book of Esther, and the Letter of St. James. The rabbinic “Parable of the King’s wine” consists of comparison, symbols, metaphors and allegory, and in its metaphorical structure presents an uncomplicated secular fictional narrative. It is concluded that the religious aesthetic charm of the Old and New Testaments and rabbinic writings encourages in-depth scientific research in the perspective of Christian-Jewish dialogue and in its existential-religious and aesthetic-literary layer seems to be of great interest today.